ANALISIS PERMINTAAN OBJEK WISATA SUNGAI HIJAU DI KABUPATEN KAMPAR DENGAN METODE BIAYA PERJALANAN - Herminto, Fredi; Aqualdo, Nobel; ', Eriyati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research was conducted on Sungai Hijau attraction in KamparRegency. The purpose of this research is to know the factors influence the demandof Sungai Hijau attraction and assess economic value of Sungai Hijau attractionby Travel Cost Method. This research using accidental sampling technique withnumber of samples was 45 visitors on Sungai Hijau attraction. Analysis method isused in this research is descriptive quantitative method. From the analysis result,regression coefficient value from the variables that influence to the total demand of Sungai Hijau attraction (Y) is travel cost (X1) by 0,000006719, income (X2) by -0,00000001207, age (X3) by -0,02, and distance (X4) by -0,019. The result from F test showed that travel cost, income, age, and distance give significant influence to the total demand of Sungai Hijau attraction. From the t test result, only variable distance give significant influence to the total demand of Sungai Hijau attraction. The influence caused (R2) by the four independent variables together to the dependent variable is 25,8%, meanwhile the rest is 74,2% influence by other variables that not covered in this research. Based on the calculation result obtained economic value of Sungai Hijau attraction by using Travel Cost Method is Rp1.213.680.000 per year. This value can be mean as loss economic value if ever damage or reduce the environment quality of Sungai Hijau attraction. Local government should be more concern to improve Sungai Hijau attraction.Keywords: demand, economic value, travel cost method